O diálogo e a afetividade no contexto da educação infantil: as pessoas grandes dizendo a sua palavra - Goelzer, Juliana (2014)
This Dissertation in Education, developed in Training, Knowledge and Professional Development line (PPGE / UFSM), was conceived as a chance to look at the education of young children as well as for the training of their teachers from the perspective of Freire's education. In this sense, the research aimed to investigate how the "big people" who work at the Pediatric Education Ipê Amarelo/ UFSM include educational / dialogic / affective relations between itself and its possible implications / impact on the education of children. Methodologically the study has a qualitative approach and fits with the kind participative research with ethnographic characteristics. This investigative process was proposed dialogue, through letters, with all the "big people" who work in the Ipê Amarelo, aiming hear them regarding the central research questions. Such writings were interpreted from a hermeneutic analysis, which allowed to interpret the different voices of these "big people" from their horizon of understanding. When identifying the different ways of understanding these "big people" about the repercussions of their relations in the education of children, and in many instances also seek to understand their silences; this process of listening paths pointed to the role of the management team that is part of the coordination and direction groups, indicating the need for further improvement of the training practices articulating all segments that make up the unit, aimed at strengthening the institution as a space of relations dialogic and affective, in which everyone understands the importance of such relationships and the responsibility of each and everyone in the educational process experienced by young children. The research also pointed to the need for teacher training considered further the specificity of such a step and the importance of coordination between the "big people" working in it.Thus educator, throughout his training, can understand the complexity of space and the people who are part of it, recognizing the importance of dialogue to be established between him and the other "big people" that context. This will make it possible for everyone to recognize the importance of relations of dialogue and affection, and that the areas of continuing education, while addressing the specifics of this step, never lose focus that together form the group responsible for the education of children.